The Application of Skin Care Product in Melasma Treatment - Wang Y; Zhao J; Jiang L; Mu Y (Dove Medical Press, 2021)
Yu Wang, Jianmei Zhao, Lu Jiang, Yunzhu Mu Department of Dermatology, The Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan Province, 637000, People's Republic of ChinaCorrespondence: Yunzhu Mu Email hymyz@126.comAbstract: Melasma is an acquired and chronic hyperpigmentation disorder which is recognized as one of the most psychologically distressing and difficult to cure forms of skin hyperpigmentation. It is associated with substantial quality of life impairments. Treatments of melasma include local application, oral medication, physical laser therapy and program combination therapy. However, routine treatment usually leads to the damage of skin barrier function, resulting in adverse reactions such as erythema, pruritus, post-inflammatory pigmentation and even scar. Skin care products contain a variety of active ingredients, which are widely concerned by cosmetic dermatologists because of high safety, good tolerance and the effect of improving the damaged skin barrier. Using skin care products alone or in combination with routine treatment not only can improve the curative effect for melasma, reduce side effects and recurrence rate, but also improve patient satisfaction. This article mainly describes the application of skin care products in the treatment of melasma.Keywords: skin care product, melasma, treatment